2010
DOI: 10.1253/circj.cj-10-0024
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell Biology - A Way to Understand the Evolution of Cardiovascular Diseases -

Abstract: Stromal cells, composed of fibroblasts, microvascular endothelial cells, immune cells and inflammatory cells, are critical determinants of the mechanical properties and function of the heart and vasculature, and the mechanisms whereby these types of cells are activated are important to understand the progression of cardiovascular diseases. Emerging studies have suggested that the activation of autocrine and paracrine signaling pathways by stromal cell-derived growth factors, cytokines and bioactive molecules c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 125 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…Traditionally, cardiac fibroblasts were defined by their morphological appearance, namely by their branched cytoplasm surrounding an elliptical, speckled nucleus that typically has 1 or 2 nucleoli. 1,2,21 However, study of cardiac fibroblasts has been challenging, and they remain poorly characterized in molecular terms. 1 One reason for this is the relative lack of serviceable fibroblast markers, because the known markers either are not specific for fibroblasts or detect only subpopulations of fibroblasts.…”
Section: Challenges Of Studying Fibroblasts In the Heartmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, cardiac fibroblasts were defined by their morphological appearance, namely by their branched cytoplasm surrounding an elliptical, speckled nucleus that typically has 1 or 2 nucleoli. 1,2,21 However, study of cardiac fibroblasts has been challenging, and they remain poorly characterized in molecular terms. 1 One reason for this is the relative lack of serviceable fibroblast markers, because the known markers either are not specific for fibroblasts or detect only subpopulations of fibroblasts.…”
Section: Challenges Of Studying Fibroblasts In the Heartmentioning
confidence: 99%
“…1,2 With their various functions, cardiac fibroblasts are at the interface of multiple interactions, playing an integral part in maintaining homeostasis in the heart. 3,4 Under physiological conditions, cardiac fibroblasts contribute to the structural, mechanical, biochemical, and electric properties of the heart.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kadner et al found that umbilical cord artery derived cells express cytoskeletal filament proteins such as alpha smooth muscle actin (ASMA) and fibroblastic vimentin and additionally show fibroblast like morphology. For this reason they were considered to be myofibroblasts [12], an intermediate cell type between fibroblast and smooth muscle cells [13,14]. A comparative study revealed that CD90, fibronectin and collagen type I expression of human umbilical cord artery derived cells is similar to that of pulmonary heart valve interstitial cells.…”
Section: Introductionmentioning
confidence: 99%
“…1215,51 Marked phenotypic alterations in fibroblast adhesion and migration have been correlated with myocardial disease. 5255 Cardiac fibroblasts can also secrete vitronectin and express vitronectin receptor α V β 3 integrin.…”
Section: Discussionmentioning
confidence: 99%